Mitigating the tradeoff between proportionality and accountability in electoral systems: Evidence from the Italian senate 1994-2006 - Matteo Alpino (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
First-past-the-post elections in single-member districts make legislators more accountable to their district of election compared to proportional electoral systems. Accountability makes politicians more sensitive to voters' preferences when deciding where and how to allocate public expenditure, and also reduces rent extraction. On the other hand, first-past-the-post elections generate overrepresentation of majority parties in parliament, potentially hurting minorities and democratic legitimacy. The mixed system used for Italian Senate elections in 1994, 1996 and 2001 mitigates this tradeoff: 3/4 of the seats are assigned to winners in single-member district elections (majoritarian tier), while the rest to the best runners-up based on party-level vote counts (proportional tier). The system mechanically compensates opposition parties, while keeping all legislators equally accountable to their district. In fact, our empirical analysis based on close elections does not find significative differences in targeting of legislative activity to the district, and in absenteeism between senators of different tiers, contrary to what other studies find for mixed systems with two separate ballot lists.
Keywords: D72; 330; electoral rules; mixed electoral systems; comparative political economy